(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This research aims to know the implementation of the financial management policies of the village of Waitina Sub-district Mangoli timur Regency Sula Islands. This research uses theories of Edward III’s policy implementation with communication indicators, resources, disposition and bureaucratic structure. This study uses qualitative methods with an informant as much as 10 people comprising the head of BPD, the village chief, officials of the customs of the village, the village Authorities and society. Research results show that financial management of the village of waitina in General has already done with effective but in demensi resources and disposition or attitude of the executor not optimal so that there is also an inhibitor of factor or constraint in financial management of the village. The dimensions of the resources and the attitude of the authorities of the village should be increased in order to improve the quality of the implementation of the financial management of the village in the village of Waitina, Sula Islands Regency Keywords: Financial Management Policy Implementation